2020
DOI: 10.3389/fonc.2020.00884
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Theranostics - An Overview

Abstract: Metastatic prostate cancer is incurable, and novel methods to detect the disease earlier and to direct definitive treatment are needed. Molecularly specific tools to localize diagnostic and cytotoxic radionuclide payloads to cancer cells and the surrounding microenvironment are recognized as a critical component of new approaches to combat this disease. The implementation of theranostic approaches to characterize and personalize patient management is beginning to be realized for prostate cancer patients. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…It was estimated that almost 1.3 million new cases of PCa were diagnosed and that 359,000 associated deaths occurred worldwide in 2018 (Bray et al, 2018). Currently, the conventional treatment modalities for PCa include surgical resection, hormone therapy, radiotherapy, and chemotherapy (Abou et al, 2020). Moreover, the dichotomy of overtreatment and tumor progression of PCa poses a new challenge for modern medicine, owing to the substantial heterogeneity of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that almost 1.3 million new cases of PCa were diagnosed and that 359,000 associated deaths occurred worldwide in 2018 (Bray et al, 2018). Currently, the conventional treatment modalities for PCa include surgical resection, hormone therapy, radiotherapy, and chemotherapy (Abou et al, 2020). Moreover, the dichotomy of overtreatment and tumor progression of PCa poses a new challenge for modern medicine, owing to the substantial heterogeneity of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, long-term androgen deprivation can ultimately lead to castration-resistant PCa (CRPC), which favors metastasis and poor prognosis (45)(46)(47). Although much effort has been made to improve PCa treatment, it is still needed to identify more sensitive biomarkers to guide early diagnosis and treatment (37,48,49). Several studies have shown that lncRNA DRAIC is dysregulated in PCa LNCaP and C4-2B cells as well as in 7 PCa tumor biopsies by androgens in a dose and time-dependent manner (14)(15)(16)(17)(18).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Radiopharmaceutical therapies (RPTs) with α-particle emitting isotopes are showing significant promise in multiple clinical and pre-clinical studies [1,2]. This cancer therapy approach sees the localized emission of cytotoxic, high linear energy transfer, helium nuclei at sites of disease.…”
Section: Introductionmentioning
confidence: 99%